Managing the invasive aquatic plant Sagittaria platyphylla (Engelm.) J.G. Sm(Alismataceae): problems and prospects - Ndlovu, Mpilonhle Sinothando (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Sagittaria platyphylla (Engelm.) J.G.Sm. (Alismataceae), commonly known as Delta arrowhead, is an invasive aquatic macrophyte native to southern United States of America (USA) that has become a serious weed in freshwater systems in South Africa, New Zealand, Australia, and recently China. In South Africa, the plant was first detected in Krantzkloof Nature Reserve, KwaZulu-Natal Province in 2008, and due to its known impact in other countries, it was listed as a Category 1a invader species under the National Environmental Management: Biodiversity Act 2004 (NEM: BA). This listing required mechanical and chemical control methods to be implemented by the South African National Biodiversity Institute's (SANBI), Invasive Species Programme (ISP), with the aim of eradicating the weed. Despite the eradication efforts, by 2016, the weed was recognized as one of the country's top 10 worst and fastest spreading invasive alien plants. Since its introduction in 2008, the plant has spread both within and between sites in South Africa, increasing from one site in 2008 to 72 sites by 2019. Once introduced into lotic systems, the plant spread rapidly downstream, in some cases up to 120km within six years, with an average of 10 km per year. Extirpation over the last ten years was only possible at a limited number of sites. Under the current management approach, the invasion is foreseen to spread to new sites within a 5 km radius of the current populations. Due to the failure of conventional control mechanisms, biological control is currently being considered as a potential control option. Four potential biological control agents are under investigation, but none have been released. Amongst them is the fruit and flower feeding weevil Listronotus appendiculatus Bohm. (Coleoptera: Curculionidae) which showed most potential as a suitable biological control agent. This study demonstrated that L. appendiculatus herbivory negatively influenced the overall fitness of S. platyphylla by reducing the plant's growth rate and above ground biomass. Listronotus appendiculatus herbivory also reduced the plant's size and the potential to kill adult plants. Most importantly, L. appendiculatus larval feeding damage significantly reduce viable-germinating seeds, the weed's primary dispersal mechanism. Therefore, a biological control programme is advised to be integrated within the current management plan.
Keywords: Aquatic weeds -- Biological control -- South Africa; Sagittaria latifolia -- Biological control -- South Africa; Noxious weeds -- Biological control -- South Africa; Invasive plants -- Biological control -- South Africa; Listronotus; Insects as biological pest control agents